Daebak Chicken Frost Sdn. Bhd / Muhammad Hazim Syahmil Rosle - Muhammad Hazim Syahmil, Rosle (2020)
For the summary of this business, we can conclude this business will success. It is because of the population around the business area. Besides, the differences concept from the other business also one of the reason of effectiveness of this project. Our society are like to buy food that easy to make but have a nutrition. They are very take care of their healthy nowadays. A healthy food can guarantee a good performance of work. So, we are here to take a chance to develop a business based on food to our society. Our product are based on the chicken. We will make a good product to serve to our customers. Other than that, our mission and vision are very clear. We want to produce a clean products and can available to all kind of customers. The chicken of our product will be marinade by our special spice and recipe. Then, it will frost to keep the quality of the marinade chicken. For all the businessman out there, before develop what kind of business they will investigate how the market potential. It is very important to know how the market potential in that area. The good market potential will give a good return to the entrepreneur. It is the reason why we choose to produce a frozen food. Our target are to deliver our product to the people who are live in the city. Most of them are not have enough time prepare a good food to the family. They are very busy with their work. With our product, they can balancing their time to do work and to cook easily and faster. While, the food served have a good quality and healthy. With all that kind of situation, our company will get double returns. Out of all the profit, we can managed to expand our branch. Next, maybe we can try to make other kind of frozen food that will easily accepted by our society. With huge profit, we can add our machineries and equipment at the shop. Or our can send some of our lucky employee to do some training at a huge company or go to seminar to gain more experience for our marketing and produce activity.